Kajian Perpustakaan Umum Rungkut Asri Kota Surabaya dengan Pendekatan Ergonomi - Putri, Resti Ananda Odie; Agustin, Dyan (Universitas Medan Area, 2024)
Surabaya City Public Library is a physical building that becomes a place or container of various types of information sources. Users or the public can utilize library facilities to fulfill their curiosity in their intellectual field or talent. A factor that can provide effective work or study quality is comfort. The concept of ergonomics, which can be interpreted as a human-centered science, can be used as one of the references in designing a library. Ergonomics is a systematic science in the utilization of human information. This information can be in the form of properties, abilities, and limitations which are then processed to design work systems effectively, safely, and comfortably. The effective method for this library research is a qualitative descriptive method. Data collection techniques applied are interviews, observations, and documentation. The data collected is then analyzed so that the data can be reduced, presented, and then a conclusion is drawn. After being presented, the results will be obtained that the Surabaya City public library almost fulfills the criteria for an ergonomic architectural approach.